IOT Based Battery Management System - Muntode, Swapnil Gaikwad; Muntode, Ketaki Pandit; Muntode, Anjum Shaikh; Muntode, Prof. Jayashri Khot (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Electric vehicles are the future of Automobile industry. The rising EV market, along with the diminishing supply of petroleum fuels, demands the development of more efficient EVs. A battery management system (BMS) is an essential component of any electric vehicle. It consists of a number of electrical and electronic circuits (including converterand inverter circuits) that have been programmed to monitor and extract the maximum output from a battery system. The chemical reactions are what determine the battery’s performance. The performance of a battery degrades as chemicals decay. As a result, these features of a battery must be regularly monitored. Because of their high charge density and lightweight, Lithium-ion batteries have proven to be a popular choice among electric vehicle producers. Despite the fact that these batteries have a lot of power for their size, they are quite unstable. It is critical that these batteries are never overcharged or discharged, requiring the use of voltage and current regulators. In this research paper, we will monitor various aspects of the vehicles like current, Voltage, SOC and temperature with the help of NodeMCU which is the Wi-fi enabled microchip that willsend the data or crucial parameters to the server which is the ThingSpeak. Therefore, inthis way we can monitor these parameters from anywhere and also monitor battery health.